Vegetius’De re militari: Military Theory in Medieval and Modern Conception - Allmand, Christopher T. (History compass, 2011)
In recent years, the De Re Militari of the Roman writer Vegetius, regarded in the Middle Ages as the authority on war, has increasingly drawn the attention of historians. Study of an important source, the marginalia on the 220 or so surviving medieval manuscripts reflecting the reactions of readers to particular passages in the text, can tell us much as to how it was read and responded to by readers in the Middle Ages, not least by Petrarch, whose annotated copy has survived to this day. Much interest has been shown in the medieval translations of the work by modern philological and textual scholars, while the historical significance of these translations has not been ignored. Through the writings of persons such as John of Salisbury, Alfonso the Wise, Giles of Rome, and Christine de Pisan, Vegetius’ ideas regarding the place and purpose of the army, the exercise of legitimate force, and the role of the soldier in achieving a peaceful society, were advanced. The practical application of what is termed Vegetian influence upon the waging of war is often debatable, and scholars are divided on issues relating to it. The military life, with the concept of it as a career, was slowly coming to be seen as one of service to society, an idea which underpinned the traditional view of chivalry. If historians do not always agree what constituted a Vegetian ‘legacy’, its part in stimulating interest in things classical, and in the military ideas and practices of the Roman world in particular, can scarcely be doubted.